2019
DOI: 10.1186/s12872-019-1215-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid and risk of cardiovascular mortality: a systematic review and dose-response meta-analysis of cohort studies of over a million participants

Abstract: Background Cardiovascular disease (CVD) is the leading cause of death worldwide. Some studies have suggested anassociation between serum uric acid levels and cardiovascular mortality; however, the results have not been summarized in a meta-analysis. Methods A comprehensive search of all related studies until April 2018was performed in MEDLINE/PubMed and Scopus databases DerSimonianand Laird random-effects models were used to combine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 48 publications
2
80
0
4
Order By: Relevance
“…[6][7][8][9][10] Whether urate elevation is involved in the pathogenesis of comorbidities seen in gout is still a debated issue, but an increasing number of epidemiological studies have found hyperuricemia as an independent risk factor for gout comorbidities: A meta-analysis including cohorts of over a million subjects shows serum urate levels to increase cardiovascular mortality risk in a dose-dependent manner, and experimental animal models show positive correlation between urate levels, arterial hypertension, and insulin resistance, with reversal of manifestation upon lowering and inhibition of urate. [6][7][8]120,121 The common link in all these diseases is the presence of sterile inflammation, with overlapping mechanisms involved in their pathogenesis. The NLRP3 pathway, associated with MSU-induced inflammation, has also been described in atherosclerosis and metabolic syndrome.…”
Section: G Out a S A Model Of Mal Adap Tive Immune Prog R Ammingmentioning
confidence: 99%
“…[6][7][8][9][10] Whether urate elevation is involved in the pathogenesis of comorbidities seen in gout is still a debated issue, but an increasing number of epidemiological studies have found hyperuricemia as an independent risk factor for gout comorbidities: A meta-analysis including cohorts of over a million subjects shows serum urate levels to increase cardiovascular mortality risk in a dose-dependent manner, and experimental animal models show positive correlation between urate levels, arterial hypertension, and insulin resistance, with reversal of manifestation upon lowering and inhibition of urate. [6][7][8]120,121 The common link in all these diseases is the presence of sterile inflammation, with overlapping mechanisms involved in their pathogenesis. The NLRP3 pathway, associated with MSU-induced inflammation, has also been described in atherosclerosis and metabolic syndrome.…”
Section: G Out a S A Model Of Mal Adap Tive Immune Prog R Ammingmentioning
confidence: 99%
“…Many studies have consistently shown that elevated uric acid levels are correlated with lower risk of PD in white men [29]. African Americans have significantly higher uric acid levels than white persons, however the relationship between uric acid levels and PD development in African Americans has not been clearly established [30].…”
Section: Phenotypic Differencesmentioning
confidence: 99%
“…UA and superoxide anion are the two main products from XO activity. Elevated levels of serum UA in humans are often associated with an increased risk of cardiovascular disease [ 229 ]. It is important to bear in mind that UA in physiological serum concentrations acts as a powerful antioxidant in the blood by scavenging ROS [ 61 , 230 ].…”
Section: Redox and Oxidative Stress In Genetic Diseases Of Connectmentioning
confidence: 99%